PELAKSANAAN PENGADAAN BARANG/JASA MELALUI E-KATALOG PEMERINTAH DI PROVINSI RIAU - Beza, Mutiara Giyana; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
E-Government gives the opportunity recently to improve the quality of government, by way of increased efficiency, new services, an increase in participation of citizens and their an increase of the global information infrastructure. One of the implementation of e-government systems through the use of information and communication technology is the procurement process government goods/ services, one of which is an e-catalog system. E-catalog aims to be the creation process of the selection of goods / services are directly so that all officers can choose the goods/ services in the selection of the best, and that efisiensi the cost and time of the election of the goods/ services from the providers of goods/services and users. In the study 's authors discuss about the actuating of procurement of goods/services through government e-catalog in the province of Riau. The purpose of the study this is to find out how the actuating of procurement of goods/services through the e-catalog of research is using the method of qualitative that is descriptive. Research is using the theory of actuating Nawawi with indicators of the direction and guidance as well as communication. Results of the study showed that the actuating of procurement of goods/services through government e-catalog in the province of Riau has not been effective because still there are some things that still have to be increased again, namely in the amount and type of product that is contained in the e- catalog and also still lack a source of power human which has a certification in management of procurement of goods the government, and the required increase in the quality of the e-catalog because technology is always experiencing growth that is rapid. Keywords : Actuating, E-Government, E-Catalog